Building on a decade of hope: Why we must champion the human experience - Jason Wolf (The Beryl Institute, 2023)
The pages of PXJ have served a primary purpose, to expand the evidence on patient experience and push the boundaries of innovation in this critical work. But through this commitment, PXJ has seen much more happen. The contributions of our thousands of authors, reviewers and editors have also fostered an environment of connection. PXJ has emerged as something more than just a journal. It has become a place for conversation. It has served as a conduit for expanding excellence in practice. It has fostered new thinking. And it has broadened our global community. There is something very special found on these pages. It is a shared sense of purpose and of possibility. And it is even more critical as our focus is ensuring excellence in the human experience in healthcare. For this reason, we thrive on the ability to share and learn, apply and evolve, act and improve. We do so with strategic focus, intentional listening, respect for differences and a commitment to agility. This carrying forth of hope and all that lies ahead is not something that just happens in the natural order of things; it takes intention and commitment, vulnerability and openness, and clarity and focus. It also takes the strength to stand up in the face of what some may say is unimportant, intangible or simply impossible. It takes champions of human experience to build on a decade of hope.